Elecciones municipales y derecho al voto de los extranjeros no comunitarios: estado de la cuestión y propuestas de reforma. - Naranjo de la Cruz, Rafael (Revista de Derecho Político, 2017)
Resumen: Este trabajo estudia el estado de la cuestión relativa al derecho al voto de los extranjeros no comunitarios en las elecciones municipales y sugiere nuevos enfoques en relación con las distintas vertientes del tema. Asimismo, propone y analiza los cambios normativos que podrían concretarse a raíz de esa nueva concepción. La cláusula constitucional de reciprocidad no obliga a excluir del derecho a los extranjeros procedentes de países que no cumplen el requisito, sino solo a tomar en consideración su concurrencia a la hora de definir su régimen normativo. Esta interpretación de la cláusula de reciprocidad abre las puertas a una atribución general del derecho fundamental mediante ley, lo que hace necesario estudiar la posible inclusión en ella de cláusulas que limiten su alcance. Finalmente se defiende que no se puede atribuir al legislador un margen de actuación más amplio al regular las condiciones de ejercicio del derecho cuando este es ejercido por un extranjero, lo que sirve para cuestionar la constitucionalidad de la exigencia de inscripción en el censo electoral a instancia de parte. Summary: 1. Introduction. 2. The constitutional reciprocity clause. 2.1 Reciprocity as a requirement. 2.2 Towards a new interpretation of the constitutional clause. 3. The problem of the source of law. 3.1 The overcoming of the international treaty as a norm of attribution of the right. 3.2 On the possibility of limiting the scope of legal recognition of the right. 3.2.1 Exclusions on grounds of nationality. 3.2.2 The criterion based on the percentage of resident foreign population. 3.2.3 The particular cases of Ceuta and Melilla. 4. Conditions for the exercise of the right to vote of foreigners in municipal elections. 4.1 Limits to legislative action. 4.2 Critical analysis of the requirement of registration in the electoral census by personal application. Abstract: This paper studies the state of the issue regarding the right to vote of non-EU foreigners in municipal elections and suggests new approaches in relation to the different aspects of the issue. It also proposes and analyzes the normative changes that could materialize as a result of this new conception. The constitutional clause of reciprocity does not oblige to exclude from the right foreigners from countries that do not fulfill the requirement, but only to take into account its concurrence when defining their regulatory regime. This interpretation of the reciprocity clause opens the door to a general attribution of the fundamental right by law, which obliges to study the possible inclusion in it of clauses that limit its scope. Finally, it is argued that the legislator cannot be given a broader scope of action when regulating the conditions of exercise of the right when it is exercised by a foreigner, which serves to challenge the constitutionality of the requirement of registration in the electoral census by personal application.